2006
DOI: 10.3354/meps323133
|View full text |Cite
|
Sign up to set email alerts
|

Clonal building, simple growth rules and phylloclimate as key steps to develop functional–structural seagrass models

Abstract: The repetitive clonal growth of the seagrasses Zostera noltii Hornem. and Cymodocea nodosa Aschers at the module level was used to implement a deterministic, individual-based, numerical model using the simplest growth rules. Inter-and intraspecific variability in plant morphology and meadow attributes was simulated, and the results yielded by the model were compared with an existing large data set recorded for both species. The model outputs showed that intra-and interspecific morphological variability can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 111 publications
3
21
0
Order By: Relevance
“…4). In agreement with Brun et al (2006), the correlation observed in Fig. 4 between PI and the relative maximum production of photosynthetic tissue suggests that there is a mechanism that modifies the AG/BG ratio.…”
Section: Mechanisms To Explain Plant Responses To Current Velocitysupporting
confidence: 71%
See 1 more Smart Citation
“…4). In agreement with Brun et al (2006), the correlation observed in Fig. 4 between PI and the relative maximum production of photosynthetic tissue suggests that there is a mechanism that modifies the AG/BG ratio.…”
Section: Mechanisms To Explain Plant Responses To Current Velocitysupporting
confidence: 71%
“…Accessibility to water column resources may also account for the maximum GR observed in HV plants. However, the effect of GR is by itself insufficient to fully explain the changes in morphometry and recruitment observed at HV, because these changes will require an additional modification of biomass allocation pattern (Brun et al 2006). According to the model developed by Brun et al (2006), the divergences observed in this study between growth and recruitment patterns (Fig.…”
Section: Mechanisms To Explain Plant Responses To Current Velocitymentioning
confidence: 92%
“…in the intertidal areas, whereas more continuous beds of Z. noltii and Cymodocea nodosa (Ucria) Ascherson thrive in the lower intertidal and shallow subtidal zones. In the study site, Z. noltii develops in denser stands but with a shorter canopy height compared to C. nodosa (see Brun et al 2006 for further details).…”
Section: Field Site Characterisationmentioning
confidence: 99%
“…Most studies have been carried out looking at the effect of light reduction on seagrass physiology, growth, or meadow attributes (see review table in Brun et al, 2006). In comparison, few studies have been devoted to investigating the effect of OM loads (Terrados et al, 1999;Cancemi et al, 2003), while the combined effects of light and OM on seagrass growth, survival and photosynthetic activity have rarely been reported (Short et al, 1995;Holmer & Laursen, 2002;Holmer et al, 2005).…”
Section: Introductionmentioning
confidence: 99%